2007
DOI: 10.1097/jcp.0b013e3180a9076c
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Impact of Switching Antipsychotic Therapy to Aripiprazole After Weight Gain

Abstract: Switching antipsychotic regimen to agents with low weight gain potential has been suggested in patients who gain excessive weight on their antipsychotic therapy. In an open-label pilot study, we evaluated the metabolic and psychiatric efficacy of switching to aripiprazole in 15 (9 men, 6 women) outpatients with schizophrenia who had gained at least 10 kg on their previous antipsychotic regimen. Individuals had evaluation of glucose tolerance, insulin resistance (insulin suppression test), lipid concentrations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
4

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 21 publications
2
29
0
4
Order By: Relevance
“…Similar to earlier results, we found that CGI-S and PANSS scores were significantly improved 12 weeks after switching (Casey et al, 2003;Kim et al, 2007). However, overall improvement does not necessarily mean a low rate of symptom worsening.…”
Section: Non-aripiprazolesupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to earlier results, we found that CGI-S and PANSS scores were significantly improved 12 weeks after switching (Casey et al, 2003;Kim et al, 2007). However, overall improvement does not necessarily mean a low rate of symptom worsening.…”
Section: Non-aripiprazolesupporting
confidence: 91%
“…Aripiprazole has been associated with minimal or no weight gain (Kane et al, 2002;Kasper et al, 2003) compared with olanzapine and most other atypical antipsychotics (McQuade et al, 2004). Using UKU and IAQ, we observed no significant changes in body weight during the trial, similar to a previously conducted switching study (Kim et al, 2007). Prolactin elevation, a frequent side effect of D 2 -blocking antipsychotics, may induce menstrual irregularities, galactorrhea, or sexual dysfunction (Maguire, 2002).…”
Section: Non-aripiprazolesupporting
confidence: 84%
See 2 more Smart Citations
“…24 Olanzapine and clozapine have been reported to activate hypothalamic AMPK pathway via H 1 receptors to increase food intake and body weight gain. 108 Olanzapine has also been reported to regulate feeding behaviour in rats by modulating histaminergic neurotransmission. 109 The role of the H 1 receptor in APD-induced weight gain has also been supported by findings that co-treatment of betahistine (an H 1 agonist and an H 3 antagonist) can significantly reduce olanzapine-induced weight gain in both schizophrenia patients and animals.…”
Section: Neuropharmacological Mechanisms For Apd-induced Weight Gain mentioning
confidence: 99%